Monetary policy and regional house-price appreciation - Daniel Cooper; María José Luengo-Prado; Giovanni Olivei (Federal Reserve Bank of Boston, 2016)
This paper examines the link between monetary policy and house-price appreciation by exploiting the fact that monetary policy is set at the national level, but has different effects on state-level activity in the United States. This differential impact of monetary policy provides an exogenous source of variation that can be used to assess the effect of monetary policy on statelevel housing prices. Policy accommodation equivalent to 100 basis points on an equilibrium real federal funds rate basis raises housing prices by about 2.5 percent over the next two years. However, the estimated effect increases to 6.6 percent during the early 2000s housing boom.
Keywords: E52; E58; E43; E44; 330